The projection of the first on the One in Plotinus’s Enneads - Bańka, Józef (Folia Philosophica, 2000)
Plotinus’s doctrine is based on henotheistic and emanative assumptions, and on this basis it develops its own methods of defining the One. This means, among other things, a transformation of the idea of the One, including its original, historically conditioned, content. In this context, the One can be conceived of only as the First, from which everything else emanates, so that in relation to it we can say that it has happened. If it exists, then it is a being in itself, and an index of itself.